NPOs and their Stakeholders’ Psychological Contracts: The Value of Implicit Expectations in Bolivia (2019)
Managing non-profit organizations (NPOs) in developing countries constitutes a challenge due to the intrinsic hardship of their missions, and the pressure of balancing their stakeholder’s interests and needs. Beyond the explicit challenges NPOs face (e.g., attracting volunteers, retaining employees, accounting to donors), we tackle the implicit obligations and returns that volunteers, employees, and donors hold towards an NPO. By introducing the concept of Stakeholder Psychological Contracts (SPC) and its three currencies (relational, transactional and ideological), we identify how each creates value for these stakeholders in a different way, using data from 409 respondents, representing 7 Bolivian NPOs. Despite the high levels of satisfaction and engagement among respondents, currencies such as Transactional Obligations in volunteers or Relational Returns in donors did not create substantial value. As predicted, Ideological returns showed relevance for all groups. However, in the case of employees, this currency shows a negative impact on satisfaction with the NPO, and engagement with the cause has no influence on their turnover intentions, as only satisfaction with the organization mediates in their intention to quit. We conclude that SPCs are a valuable concept for NPO managers when it comes to triggering engagement and satisfaction for each stakeholder group.